Prediction of Structure and Function of a Novel β-Lactamase Protein in Gram-Negative Bacteria Using Homology Modeling and Molecular Docking - Kiranasari, Ariyani; Dwira, Surya; Merizka, Engla (Indonesian Journal of Medical Chemistry and Bioinformatics, 2026)
The emergence of β-lactamase–producing Gram-negative bacteria represents a major global challenge due to increasing resistance to β-lactam antibiotics. In this study, we performed in silico structural and functional prediction of a newly identified β-lactamase protein sequence obtained from a Gram-negative bacterial isolate. Homology modeling was used to construct a reliable 3D model of the protein based on structurally resolved β-lactamases. The model was further evaluated using stereochemical validation parameters. Molecular docking was conducted to assess binding affinity and interaction patterns between the predicted β-lactamase and clinically relevant β-lactam antibiotics, including ampicillin, cefotaxime, and imipenem. The results revealed conserved catalytic residues typical of class A β-lactamases, strong binding affinities toward penicillin and cephalosporin substrates, and key hydrogen bond interactions within the active site. This study provides a structural framework for understanding the function of the new β-lactamase and offers insights for developing β-lactamase inhibitors targeting resistant Gram-negative pathogens.